Characterization of Peronosclerospora maydis and Its Effect on Plant Growth and Disease Incidence Under Fungicides Treatment on Maize (Zea mays L.) - Elzahra Nadya Putri; Rina Sri Kasiamdari (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractDowny mildew disease on maize (Zea mays L.) is generally caused by fungi from the genus Peronosclerospora. This study aims to identify the type of fungi that cause downy mildew in Sleman, to determine the effect of a fungicide on the growth of maize plants, the disease incidence, and severity. Fungi isolates were taken from the maize plantation area in Tirtoadi Village, Sleman. Observation of fungal spores was carried out using a binocular microscope. Application of metamorph (PMD), metalaxyl (PMMe), propineb (PMP), and mancozeb (PMMz) fungicides was carried out when the plants were 7 days after planting (DAP). Maize plants were inoculated with downy mildew spores when the plants were 8 DAP. The parameters measured were plant height, number of leaves, fresh weight, dry weight, disease incidence, and severity. Data were analyzed by ANOVA using SPSS version 23 and tested by Duncan Multiple Range Test (DMRT). The results showed that the fungi causing downy mildew in Sleman was Peronosclerospora maydis. Plants treated with mancozeb (PMMz) had the highest growth in plant height, number of leaves, fresh weight, and dry weight, followed by PMP, PMD, and PMMe treatments. The results of the DMRT test showed that the disease incidence and disease severity of PMD, PMMe, and PMP were significantly reduced compared to the P. maydis (PM) treatment. Plants with metalaxyl treatment had the highest ability to reduce disease severity by 92.70%, followed by prominent at 78.10%, metamorph 58.66%, and mancozeb 16.79%.AbstrakPenyakit bulai pada tanaman jagung (Zea mays L.) umumnya disebabkan oleh jamur dari genus Peronosclerospora. Penelitian ini bertujuan untuk mengidentifikasi jenis jamur penyebab penyakit bulai di Sleman, mengetahui pengaruh fungisida terhadap pertumbuhan tanaman jagung, kejadian, dan keparahan penyakit. Isolat jamur diambil dari area persawahan Desa Tirtoadi, Sleman. Pengamatan spora jamur dilakukan dengan menggunakan mikroskop binokuler. Pemberian fungisida dimetomorf (PMD), metalaksil (PMMe), propineb (PMP), dan mankozeb (PMMz) dilakukan saat tanaman berumur 7 hari setelah tanam (HST). Tanaman jagung diinokulasi dengan spora bulai pada saat tanaman berumur 8 HST. Parameter yang diukur adalah tinggi tanaman, jumlah daun, berat basah, berat kering, kejadian penyakit, dan tingkat keparahan. Data dianalisis dengan ANOVA menggunakan SPSS versi 23 dan diuji dengan Duncan Multiple Range Test (DMRT). Hasil penelitian menunjukkan bahwa jamur penyebab bulai di daerah Sleman adalah P. maydis. Tanaman dengan perlakuan PMMz memiliki pertumbuhan tinggi tanaman, jumlah daun, berat basah, dan berat kering tertinggi, diikuti dengan perlakuan PMP, PMD, dan PMMe. Hasil uji DMRT menunjukkan angka kejadian penyakit dan keparahan penyakit pada perlakuan PMD, PMMe, dan PMP menurun secara signifikan dibandingkan dengan perlakuan P. maydis (PM). Tanaman dengan perlakuan metalaksil memiliki kemampuan terbaik dalam menurunkan keparahan penyakit sebesar 92,70%, kemudian propineb 78,10%, dimetomorf 58,66%, dan mankozeb 16,79%.